Pengaruh Penggunaan Selebriti pada Iklan Cetak terhadap Brand Awareness pada Konsumen Remaja - Sri Maria Radeningsih; Bertina Sjahbadhyni (Fakultas Psikologi Universitas Pancasila, 2010)
Brand awareness is the first step to reach communication goal in advertising (Kelly in Wells, Burnett, Moniarty, 1998). To reach the goal, advertising should be created as interesting as possible to get viewer's attention by using, among others, celebrity endorsement. However, the use of celebrities in ads has often been argued by advertising practitioner and marketer. This study used quasi experimental method with 72 participants divided into two groups, i.e. experimental group and control group. Eight commercials samples using celebrities were given to the first group, while the other group got ad samples without celebrities. Selection of celebrity was based on Q rating. Brand awareness was measured using brand recall test, a free recall type which was introduced by Rositter and Percy. The subjects were asked to repeat the product, brand, headline, slogan and illustration which were just shown to them. The data was analyzed by comparing t test of the two groups. The result demonstrated that celebrity appearance in ad gave significant influence towards teenage buyers. This was indicated by value t=2.170, p=0.03 (p<0.05). Of four aspects that we recalled, brand and headline recall the highest score and gave headline recall score was t=3.452 p=0.001 (p<0.05).